Distraction index and Norberg angle to distinguish dysplastic and non-dysplastic hips based on FCI score - Klever, Julius; Brühschwein, Andreas; Meyer-Lindenberg, Andrea (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2020)
Objective Radiographic hip scoring according to the Fédération Cynologique Internationale (FCI) and PennHIP (Pennsylvania Hip Improvement Program) method was performed with the purpose to compare the PennHIP and FCI results as well as coxofemoral joint laxity by correlation of Norberg angle and distraction index measurements.Materials and methods A total of 167 dogs of various breeds presented for official screening examination in a veterinary teaching hospital in Germany were included. Using receiver operating characteristic analysis, the best Norberg angle and distraction index cut-off values to distinguish between dysplastic and non-dysplastic groups based on FCI grades and to distinguish between lax and tight hip joints according to the PennHIP proposal were calculated.Results More than one third (38.2 %) of dogs that passed the breeding criterions according to FCI (grades A and B) were in the half of the population with lax hip joints and should not be used for breeding according to the PennHIP proposal. A cut-off value for the distraction index of 0.44 with sensitivity of 82.7 % and specificity of 84.2 % was superior to the best cut-off value for the Norberg angle at 101.8° with sensitivity of 82.7 % and specificity of 71.9 % to discriminate between non-dysplastic joints (A, B) and dysplastic joints (C, D, E).Conclusions and clinical relevance Our results show a limited impact of laxity on the FCI grading. Breeding selection processes that are based on the FCI method could profit by an additional and complementary use of the distraction index.
Keywords: Dog; hip dysplasia; radiography; PennHIP; Fédération Cynologique Internationale